KEPEMIMPINAN USMAN BIN AFFAN - Armyn Hasibuan (IAIN Padangsidimpuan, 2018)
Usman bin Affan was chosen as the third khlaifah and was installed on 1 Muharram 24 H to coincide November 7 644 M. His leadership was quite proud of the first six years, because whatever programs and achievements the second caliph could he continue, maintain, and develop with renewal in other fields. The field of administration made during the time of Umar bin Khattab was continued and various expansions continued as well even by taking other areas as an addition and expansion. Armed forces in the field of maritime were created to be able to beat and conquer the Romans who wanted to regain control of Alexandria, Egypt, and the surrounding area. The success can be lost no longer remembered, due to slander and the crime of other people, both friends and opponents.Keyword: Leadership, Usman bin Affan, Nepotism.